Menyuarakan Hak tanpa Sekat: Sebuah Ekspresi Gerakan Sosial Petani - Ahmad Izudin (JSW (Jurnal Sosiologi Walisongo), 2019)
This paper highlighted the social change of peasant in the process of facing any struggling movement. Applying a qualitative method and case study approach, the data in this research were collected by observation, interview, and document study. The data were analyzed using the theory of “Social-Economic Morality”. By analyzing the data using this theory this article revealed the changing society in terms of peasant political attitude. This research found three important aspects. Firstly, compromise is a kind of strategy applied by peasants in their movement. Because there are no supporting factors for peasants to avoid the state’s hegemony and exploitation, so the only strategy to deal with the expansive tendency of capitalism is by changing the political attitude of peasants. Secondly, the organizational consolidation is claiming peasant’s rights. Thirdly, capacity development through the empowerment process is a form of compromise way of peasants’ movement. These three compromise models are the ways to avoid conflict to escalate.